MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL MIND MAPPING DI KELAS V SD - Eko Febri Syahputra Siregar (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to improve students’ learning outcomes through the use of mind mapping model on the local Civics in fifth grade SD Negeri 101736 Medan Krio academic year 2017/2018. This type of this study is a classroom action research (PTK). The tools used in collecting the data are tests and observations that done during the learning process takes place. This study was conducted with two cycles. The results of this study show that the use of mind mapping model in the first cycle, are the students who got the score below the minimum completeness as many as 17 students (42,5%) and the students who got the score above the completeness as many as 23 students (57,5% ) with an average value of 71,00. On the second cycle, there is a very drastic increase that all students (40 students) have completed in obtaining the desired learning outcomes and no more students are not complete. The average value obtained is 91,63. Thus it can be concluded that the use of mind mapping model can improve students’ learning outcomes.